Analysis of the Realization and Contribution of Non-Tax State Revenue (PNBP) by Service Type at the Karangantu Class III Port Authority Unit in 2024 - Claudia Ode, Chintya Putri; Nugraha, Bugi; Eddi; Dahri, Muh. (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This study aims to analyze the realization and contribution of Non-Tax State Revenue (PNBP) based on service types at the Class III Port Authority Unit (UPP) Karangantu in 2024. The research focuses on: (1) revenue realization by service groups, (2) monthly realization trends and factors influencing fluctuations, (3) the contribution of each service type, and (4) the level of achievement of the 2024 Non-Tax State Revenue target. The study employs a quantitative descriptive method using secondary data obtained from official 2024 Non-Tax State Revenue reports. Data collection techniques include documentation, observations conducted during onshore practice, and informal interviews. Data analysis covers the calculation of realization percentages, contribution levels, monthly trends, and comparisons between revenue targets and actual achievements. The results indicate that the total realization of Non-Tax State Revenue in 2024 amounted to Rp 4,716,520,673, with revenue trends fluctuating throughout the year. The highest realization occurred in April, while the lowest was recorded in July. Contribution analysis shows that navigation aids services contributed the largest share (47.3%), followed by port services (45.8%). The achievement level of Non-Tax State Revenue reached 207.90% of the target, categorizing the performance as highly effective. This study concludes that the Class III Port Authority Unit Karangantu successfully managed Non-Tax State Revenue throughout 2024. The findings are expected to serve as evaluation material and support strategic planning for revenue improvement in the following year.